2022
DOI: 10.47836/pjssh.30.4.05
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Inter-Relationship of Residential Neighborhood Characteristics on Quality of Life of Elderly

Abstract: The aspects of spatial planning have been aimed at supporting older people to stay healthy and active in their daily lives, as well as to improve their overall quality of life. Older people require accessible and functional venues and social environments that suit their emotional needs and goals. However, there has been limited study on the most significant characteristics of residential settings that impact the well-being of elderly inhabitants. This study aims to provide a comprehensive review of neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In particular, the health dimensions have already been adequately covered in other studies [17,35,36,42], with most studies using self-reported surveys as the methodology [35,36,42]. An increasing number of studies on residential housing environments, offering a similar emphasis to that of the current study, have focused on the importance of a sense of harmony [14,18,43,44]. In Turkey, Kayseri [43] revealed, in a recent study, that the most influential factors on the overall QoL of individuals living in different residential neighborhoods were satisfaction with a neighborhood, neighborhood relations, and urban services.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In particular, the health dimensions have already been adequately covered in other studies [17,35,36,42], with most studies using self-reported surveys as the methodology [35,36,42]. An increasing number of studies on residential housing environments, offering a similar emphasis to that of the current study, have focused on the importance of a sense of harmony [14,18,43,44]. In Turkey, Kayseri [43] revealed, in a recent study, that the most influential factors on the overall QoL of individuals living in different residential neighborhoods were satisfaction with a neighborhood, neighborhood relations, and urban services.…”
Section: Discussionmentioning
confidence: 89%
“…However, over the past few decades, there has been a shift in the overall perception of QoL, and numerous studies have emphasized the significance of built environments (both indoor and outdoor) in determining QoL [8][9][10][11][12], as the built environment can stimulate a safe environment; provide income opportunities; and support health, education, and recreation [2]. Lots of previous research has been carried out on the built environment and QoL in institutional settings with older or vulnerable user groups [13][14][15][16][17]. There is also a substantial amount of research addressing the notion of sustainable development and its relationship with QoL on macro levels (theoretical and political), e.g., for municipalities, communities, and neighborhoods [1,4,5,9,11,18].…”
Section: Introductionmentioning
confidence: 99%